Redefining education for a changing climate: How TTU is shaping climate-smart leaders to make it more dynamic - Nzuki, Esther Ndumi; Gichunge Kathure, Karen; Anne Kambura; Ogutu, Elizabeth; Nderi, Alex Nduah (2025)
Climate-Smart Agriculture (CSA) offers a pathway to resilience, but its success hinges on education that translates knowledge into action. Taita Taveta University (TTU) is redefining agricultural education by embedding CSA and Rangeland Ecosystem Management into its curricula through a rigorous co-creation process with stakeholders, supported by AICCRA. Leveraging its unique position as a “living lab” encompassing Kenya’s diverse agro-ecological zones, TTU equips learners with practical skills and strategic tools to address climate and food security challenges. Programs emphasize experiential learning, blending theory with hands-on application in areas such as banana tissue culture and sustainable rangeland management. These initiatives foster innovation, job readiness, and direct farmer benefits, while aligning with national development goals. TTU’s approach demonstrates how academia, policy, and practice can converge to build climate-smart leaders and catalyze resilience for Kenya’s sustainable future.